Profil Life Skills Siswa Kelas VIII MTS Fatahilah pada Materi Sistem Pencernaan - Chabibah, Chabibah; Hayat, Muhammad Syaipul; Nugroho, Ary Susatyo; Roshayanti, Fenny (PGRI Kota Semarang, 2024)
This research aims to determine the life skills profile of madrasah students, especially in learning science and digestive material. This research used descriptive quantitative methods with a sample of class VIII MTs Fatahilah Semarang. Data was obtained from questionnaires and tests. The research results show that the life skills profile of madrasah students is still not optimal, as indicated by the average being in the medium category (34.16). Madrasah students' life skills are not optimal, one of which is caused by teachers who have not developed learning that can develop students' potential optimally, especially life skills. This research is limited to the locus and perspective used so that further research can be carried out with a wider locus and perspective of madrasa students in responding to more complex future challenges that it will give birth to more comprehensive research.